Evolutionary Changes in DnaA-Dependent Chromosomal Replication in Cyanobacteria - Ohbayashi, Ryudo; Hirooka, Shunsuke; Onuma, Ryo; Kanesaki, Yu; Hirose, Yuu; Kobayashi, Yusuke; Fujiwara, Takayuki; Furusawa, Chikara; Miyagishima, Shin-ya (Frontiers in Microbiology, 2020)
Replication of the circular bacterial chromosome is initiated at a unique origin (oriC) in a DnaA-dependent manner in which replication proceeds bidirectionally from oriC to ter. The nucleotide compositions of most bacteria differ between the leading and lagging DNA strands. Thus, the chromosomal DNA sequence typically exhibits an asymmetric GC skew profile. Further, free-living bacteria without genomes encoding dnaA were unknown. Thus, a DnaA-oriC-dependent replication initiation mechanism may be essential for most bacteria. However, most cyanobacterial genomes exhibit irregular GC skew profiles. We previously found that the Synechococcus elongatus chromosome, which exhibits a regular GC skew profile, is replicated in a DnaA-oriC-dependent manner, whereas chromosomes of Synechocystis sp. PCC 6803 and Nostoc sp. PCC 7120, which exhibit an irregular GC skew profile, are replicated from multiple origins in a DnaA-independent manner. Here we investigate the variation in the mechanisms of cyanobacterial chromosome replication. We found that the genomes of certain free-living species do not encode dnaA and such species, including Cyanobacterium aponinum PCC 10605 and Geminocystis sp. NIES-3708, replicate their chromosomes from multiple origins. Synechococcus sp. PCC 7002, which is phylogenetically closely related to dnaA-lacking free-living species as well as to dnaA-encoding but DnaA-oriC-independent Synechocystis sp. PCC 6803, possesses dnaA. In Synechococcus sp. PCC 7002, dnaA was not essential and its chromosomes were replicated from a unique origin in a DnaA-oriC independent manner. Our results also suggest that loss of DnaA-oriC-dependency independently occurred multiple times during cyanobacterial evolution and raises a possibility that the loss of dnaA or loss of DnaA-oriC dependency correlated with an increase in ploidy level.